RELATIONSHIP QUOTES AS A SENSE-GIVING MEDIUM: A STUDY OF EMOTIONAL INTERACTION AND PERCEPTION ON TIKTOK - Januar Aditya Putra; Veranus Sidharta (Jurnal Ranah Komunikasi, 2025)
This study aims to explore how relationship quotes on TikTok function as a sense-giving medium in shaping users’ emotional meaning-making. In the digital era, social media has become a dynamic space where individuals express, reframe, and validate their relational experiences. Using a qualitative phenomenological approach and NVivo-assisted thematic analysis, data were collected from five active TikTok users who frequently engage with relationship quote content. The findings reveal that such content is not merely consumed passively but serves as a trigger for emotional reflection, self-expression, and collective meaning construction. Digital interactions such as commenting, sharing, and creating duets foster sensemaking processes, allowing users to exchange perspectives and build an interconnected emotional ecosystem. These quotes offer a safe space for emotional expression, particularly for female users, while also raising issues such as narrative bias and unrealistic relational expectations. Thus, relationship quotes on TikTok function as a bridge between individual emotions and collective emotional consciousness in digital communication spaces. This study highlights the importance of emotional literacy in navigating the emotionally charged content landscape of social media.